Peran Pondok Pesantren Miftahul Ulum dalam Perlindungan Anak Persepektif Fiqih Hadanah Madzhab Syafi’iyah - Subhan; Mufti Kamal (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This study examines how Pondok Pesantren Miftahul Ulum contributes to protecting children by applying principles from hadanah fiqh in the Shāfiʿī tradition. This pesantren not only functions as an Islamic educational center, but also acts as an alternative caregiving environment for minors separated from parental supervision. Using a qualitative case study methodology, the findings indicate that the implemented caregiving framework upholds central hadanah principles such as ethical role modeling, emotional support, and structured hierarchical supervision. Nonetheless, the institution continues to face specific obstacles: insufficient physical infrastructure, the absence of formal child protection protocols, and constrained access to specialized training for caregivers. To overcome these challenges, it is imperative to develop institutional capacity and codify caregiving systems in line with Islamic legal norms. This study contributes both conceptual and practical guidance for enhancing child-rearing approaches in salafiyah pesantren contexts. Additionally, the research underscores the necessity of ongoing evaluation, enhanced collaboration with families and community stakeholders, and strengthened governance mechanisms to ensure a coherent, sustainable, and effective child protection strategy in religious educational settings.